2003
DOI: 10.1086/376536
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression ofCandida albicansSecreted Aspartyl Proteinase and Phospholipase B Genes in Humans Correlates with Active Oral and Vaginal Infections

Abstract: The in vivo expression of Candida albicans secreted aspartyl proteinase (SAP1-SAP8) and phospholipase B (PLB1 and PLB2) genes was analyzed in 137 human subjects with oral and vaginal candidiasis or carriage. Total RNA was isolated from whole unstimulated saliva or vaginal swabs, and the expression of SAP1-8 and PLB1-2 was evaluated by reverse-transcriptase polymerase chain reaction using specific primer sets. A spectrum of SAP gene expression profiles was obtained from different C. albicans strains during symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
174
3
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 186 publications
(191 citation statements)
references
References 48 publications
9
174
3
5
Order By: Relevance
“…colonization, among inhibitory microbial flora, to frequent occurrence of asymptomatic oral and vaginal carriage, and to virulence in immunocompetent and immunodeficient hosts, are poorly understood. In previous work, we have found that expression of specific secreted aspartyl proteinase (SAP) genes is correlated with active disease and anatomical location, whereas expression of other SAP genes reflects the presence of the organism but not disease (Naglik et al, 2003).Hyphal wall protein (Hwp1), a transglutaminase substrate which functions as an adhesin, is important for the pathogenesis of candidiasis (Staab et al, 1996(Staab et al, , 1999Sundstrom et al, 2002). HWP1 mRNA and protein are abundant in hyphae in vitro, and greatly reduced or undetectable in yeast forms (Staab et al, 1996(Staab et al, , 1999 Sharkey et al, 1999;Nantel et al, 2002).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…colonization, among inhibitory microbial flora, to frequent occurrence of asymptomatic oral and vaginal carriage, and to virulence in immunocompetent and immunodeficient hosts, are poorly understood. In previous work, we have found that expression of specific secreted aspartyl proteinase (SAP) genes is correlated with active disease and anatomical location, whereas expression of other SAP genes reflects the presence of the organism but not disease (Naglik et al, 2003).Hyphal wall protein (Hwp1), a transglutaminase substrate which functions as an adhesin, is important for the pathogenesis of candidiasis (Staab et al, 1996(Staab et al, , 1999Sundstrom et al, 2002). HWP1 mRNA and protein are abundant in hyphae in vitro, and greatly reduced or undetectable in yeast forms (Staab et al, 1996(Staab et al, , 1999 Sharkey et al, 1999;Nantel et al, 2002).…”
mentioning
confidence: 99%
“…Hypha-specific expression of Hwp1 extends to fungal growth in the host, as shown by the presence and absence of Hwp1 on hyphae and yeast, respectively, in candidiasis of the murine stomach (Sundstrom et al, 2002). To gain insight into the relationship between HWP1 gene expression and commensalism or symptomatic tissue invasion, we analysed the same carrier and candidiasis specimens that had been used previously to determine SAP and PLB gene expression in samples of whole unstimulated saliva and vaginal swabs (Naglik et al, 2003) supported a potentially important role for hyphal forms in asymptomatic infections with C. albicans. …”
mentioning
confidence: 99%
See 3 more Smart Citations